Swarm の磁場計測を用いた極冠オーロラ近傍の電流系に関する研究 - 山内, 淑寛; 細川, 敬祐; 大谷, 晋一; 塩川, 和夫; 大塚, 雄一; Toshihiro, Yamauchi; Keisuke, Hosokawa; Shinichi, Otani; Kazuo, Shiokawa; Yuichi, Otsuka (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object